Managing public pension plans : decisions, challenges, and reforms - Chen, Gang; Hoang, Trang (Public Administration); Ebdon, Carol (Routledge, 2025)
This book provides an in-depth explanation of public pension plan management and the decision-making processes surrounding pension policies within state and local governments in the United States. It addresses the intricate balance between securing retirement benefits for public employees and ensuring the fiscal sustainability of pension systems and their sponsoring governments. The book begins with an introduction to the purpose and significance of public pension systems, establishing a foundation for understanding key pension decisions. Using a logic model framework, the authors assess how environmental factors, stakeholders, and legal constraints shape decisions in pension management. The book identifies five core goals for public pension management - benefit sufficiency, cost affordability, funding sustainability, asset management efficiency, and governance quality - emphasizing the relationships among these objectives.Detailed chapters cover investment policies, actuarial processes, and the design of benefits and contributions, explaining the financial and actuarial bases necessary for sound pension decisions. Pension reform efforts, including the transition from defined benefit plans to defined contribution, cash-balance, and hybrid plans, are examined in depth, highlighting the reasons for reforms and analyzing their impacts on the employees and employers. The book concludes with ten takeaways for effective pension plan management and addresses emerging challenges such as fiscal pressures, inflation, and changing demographics. With practical implications grounded in research, this book serves as an essential resource for pension board members, pension system administrators, government officials, legislators and their staff, professionals, researchers, and students involved in public pension plan management.
Keywords: Pension trusts -- Management.; Pensions.; elektronické knihy; electronic books